Pengaruh Efikasi Diri Terhadap Perencanaan Karir Dengan Motivasi Sebagai Variabel Mediasi Studi Kasus Pada PT.Kali Rejo Lestari Lampung Tengah - Septiana, Nani; Suwarto, Suwarto; Saputra, Satria Dwi Nuvanur (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the effect of self-efficacy on employee career planning withcareer motivation as a mediating variable. This type of research is a quantitative study with apopulation of 97 employees registered at Kalirejo Lestari, Central Lampung, only 78 samplesused in accordance with predetermined criteria. The data used is secondary data distributionof questionnaires in the form of a list of questions with several alternative answers forrespondents. The statistical test used to test the hypothesis is multiple linear regressionanalysis and tested using the statistical packages for the social science (SPSS) version 26program. Based on the results of statistical tests indicate that self-efficacy, career planninghas a positive and significant influence on career motivation.